2006
DOI: 10.1002/eqe.608
|View full text |Cite
|
Sign up to set email alerts
|

Buckling-restrained brace using steel mortar planks; performance evaluation as a hysteretic damper

Abstract: SUMMARYThe authors developed a buckling-restrained brace that enables increased design freedom at both ends of the core plate and strict quality control while providing stable hysteresis characteristics even under high strains. The buckling-restrained brace can be formed by welding a core plate covered with unbonded material to a pair of mortar-filled channel steels (steel mortar planks) as a restraining part. The use of this approach enables visual confirmation of the status of the mortar filling and also fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
86
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(86 citation statements)
references
References 0 publications
0
86
0
Order By: Relevance
“…Several enhancements to BRBs have been proposed recently in order to improve their implementation in practical applications (e.g. Iwata and Murai, 2006;Zhao et al, 2010). Experimental tests on buckling restrained braces (BRBs), as isolated members, have demonstrated that these devices possess high energy dissipation capacity by means of stable and symmetric hysteretic loops when they are subjected to cyclic loads, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several enhancements to BRBs have been proposed recently in order to improve their implementation in practical applications (e.g. Iwata and Murai, 2006;Zhao et al, 2010). Experimental tests on buckling restrained braces (BRBs), as isolated members, have demonstrated that these devices possess high energy dissipation capacity by means of stable and symmetric hysteretic loops when they are subjected to cyclic loads, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental tests on buckling restrained braces (BRBs), as isolated members, have demonstrated that these devices possess high energy dissipation capacity by means of stable and symmetric hysteretic loops when they are subjected to cyclic loads, e.g. (Merrit et al, 2003;Black et al, 2004;Uang and Nakashima, 2004;Iwata and Murai, 2006;Zhao et al, 2010). However, experiments are still needed in order to corroborate their good behaviour when located in actual building frames subjected to seismic loads.…”
Section: Introductionmentioning
confidence: 99%
“…The BRB is fixed (Iwata and Murai, 2006;Tsai and Hsiao, 2008;Chou and Chen, 2010) or pinned to a frame in high rise buildings, and the pinned BRBs (Fahnestock et al, 2007;Wigle and Fahnestock, 2010;Zhao et al, 2012b) are the focus of this study.…”
Section: Introductionmentioning
confidence: 99%
“…For the pinned BRBs, to ensure that the yield region of a single core plate is well restrained by the external member, it is reinforced before the core comes out of the external member (Chen et al, 2001;Qiang, 2005;Iwata and Murai, 2006). Thus, there are three distinct failure modes of pinned BRBs: (1) Bending failure around the extended core region due to its insufficient load-bending capacity (Zhao et al, 2011); (2) Overall buckling failure due to deficient external member bending stiffness (Ju et al, 2009;Zhao et al, 2012a);and (3) Local press failure at the external member end due to significant stiffness weakening or immense contact force.…”
Section: Introductionmentioning
confidence: 99%
“…1(a). To date, many investigations have been conducted on the seismic performance of BRBs [2,[14][15][16][17][18][19][20][21]. Unfortunately, few works attempted to evaluate the evolution of core member deformations and contact force distribution between core and external components, which in fact, is key to understanding the mechanical, also energy dissipation mechanism of BRBs.…”
Section: Introductionmentioning
confidence: 99%